Analysis of the inventory and quantification of geomorphosites of Capadócia Piauiense (PerCursos, 2022)
The inventory and the quantification of an area makes it possible to identify places with elements endowed with superlative values (scientific, tourist, aesthetic, cultural, economic and others), which differentiate them from the other parts that constitute geodiversity, it also allows, determining the relevance of these places and the need to preserve them. This article aims to analyze the results obtained from the inventory and the quantification of geomorphosites in Capadócia Piauiense, located in the Immediate Geographic Region of Picos, state of Piauí. The methodology included bibliographic research and theoretical analysis, field research, making cartographic material and qualitative and numerical assessment of the geomorphosites in the area. The results show that Capadócia Piauiense has outstanding geodiversity and geomorphosites endowed with scientific, aesthetic, ecological, cultural, economic, tourist and didactic/educational values, however such places need greater appreciation, dissemination, and, especially, strategies of geoconservation that could minimize the risks of its deterioration.
Keywords: inventory; quantitative study; geoheritage; Cidade de Pedras; Piauí